(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2013)
This article discusses the mechanism for distribution of estate land mechanism with a focus on the problems faced in the distribution of inheritance in Felda Taib Andak. Data in this article are obtained quantitatively and qualitatively. In this study, field work was done through interviews and questionnaires. Interviews were done directly with the persons involved in the distribution of FELDA estates that include the management of FELDA Taib Andak. The questionnaire was distributed to 250 Felda settlers of Taib Andak. Only a total of 209 (83.6 per cent) returned the questionnaire. The study showed that most of the settlers had elected to appoint the administrators as the mechanism for FELDA estate distribution than giving direct ownership to mutually agreed party or parties among the heirs. The study has also shown that contentious issues in the estate distribution in Taib Andak are provisions of sections 14 and section 15, the Land (Group Settlement Areas) Act 1960 which only allow for two nominees to be named in the FELDA title deed. In addition, the incidence of fraud and disputes among heirs and other issues have also contributed to the problems in the distribution of estates. However, this study has revealed that the main problem in the implementation of distribution of FELDA estates is due to the attitude of the parties involved in the matter. Keywords: FELDA inheritance, Land Act 1960, the Islamic inheritance, Islamic Law